Comparação de métodos de fenotipagem em soja e variabilidade genética de Macrophomina phaseolina - Panisson, Francine Talia (2019)
Charcoal rot, caused by Macrophomina phaseolina, is a radical and important disease in soybean cultures, associated with droughts and high temperatures. The use of resistant cultivars is of utmost importance to deal with diseases, as a total genetic resistance to the pathogen, in Brazilian soybean cultivars, was still not identified. A resistant material selection can supply useful sources for programs to improve soybean breeding. This work aims to a) evaluate phenotyping methods in soybean to eliminate charcoal rot; b) evaluate the genetic variability of M. phaseolina. In chapter one, 23 isolates of fungi were inoculated in three soybean cultivars by using cut stem method. Later, two selected isolates were inoculated in 20 soybean cultivars by cut stem, sand layers, mycelium layer, and inoculum aggregate to the soil. These two isolates were also inoculated, by using the cut stem method, in 12 soybean genotypes, 11 of them were classified as, moderately, resistant, and one was susceptible to fungus. By using the cut stem method, the extension of stem necrosis was evaluated and the relative area below the progress curve of the disease calculated (RABCD). In the remaining inoculation methods, five fragments from the main root and from the stem of the plants were isolated to evaluate the intensity of the disease by the incidence of micro- sclerotia and by the severity (fragment of micro-sclerotia). The analyses were carried out using an R Software, and means test by Scott-Khott, with a significance level of 5% (p<0.05). Aggressiveness was present among M. phaseolina isolates, the most aggressive ones were CMES 1169 and Mp CX which allowed their inclusion in resistance studies to soybean genotypes to fungus. The soybean cultivars presented distinct severity reaction to charcoal rot when the method of inoculation of sand layers, and cut stem was used; the last one being efficient to select useful source to develop soybean genotypes with higher levels of resistance to charcoal rot, due to prompt answer and execution. The soybean cultivars TMG 7062 and V -Mas, and soybean genotypes DT97-4290, and PI 567334, consistently, presented small ARACPC with cut stem method. These materials can be included in breeding programs for resistance to charcoal rot in soybean. In chapter II, the genetic variability of 23 M. phaseolina isolates was characterized by the molecular markers of amplified fragment length polymorphism (AFLP). The amplified fragments were analyzed in Polyacrylamide at 7% and translated into binary data, indicating presence (1) or absence (0). The cluster analysis was carried out with unweighted pair group method with arithmetic mean (UPGAM) and the genetic distance by Jaccard coefficient, considering the genetic variation within and among the populations from different hosts, geographic origin (State of Brazil), and year the isolates were collected. The genetic variability analysis showed high variability among the M. phaseolina isolates, related to the host, the geographic origin and the year of the collection. The results indicated perspective of study reaction of soybean genotypes to the pathogen and to gene identification which ensure resistance, with possibility of incorporation of selected soybean genotypes.